Calcium-Sensing Receptor Gene: Regulation of Expression - Hendy, Geoffrey N.; Canaff, Lucie (Frontiers in Physiology, 2016)
The human calcium-sensing receptor gene (CASR) has 8 exons, and localizes to chromosome 3q. Exons 1A and 1B encode alternative 5’-untranslated regions (UTRs) that splice to exon 2 encoding the AUG initiation codon. Exons 2-7 encode the CaSR protein of 1078 amino acids. Promoter P1 has TATA and CCAAT boxes upstream of exon 1A, and promoter P2 has Sp1/3 motifs at the start site of exon 1B. Exon 1A transcripts from the P1 promoter are reduced in parathyroid tumors and colon carcinomas. Studies of colon carcinomas and neuroblastomas have emphasized the importance of epigenetic changes – promoter methylation of the GC-rich P2 promoter, histone acetylation – as well as involvement of microRNAs in bringing about CASR gene silencing and reduced CaSR expression. Functional cis-elements in the CASR promoters responsive to 1,25-dihydroxyvitamin D [1,25(OH)2D], proinflammatory cytokines, and the transcription factor glial cells missing-2 (GCM2) have been characterized. Reduced levels of CaSR and reduced responsiveness to active vitamin D in parathyroid neoplasia and colon carcinoma may blunt the “tumor suppressor” activity of the CaSR. The hypocalcemia of critically ill patients with burn injury or sepsis is associated with CASR gene upregulation by TNF-alpha and IL-1beta via kappaB elements, and by IL-6 via Stat1/3 and Sp1/3 elements in the CASR gene promoters, respectively. The CASR is transactivated by GCM2 – the expression of which is essential for parathyroid gland development. Hyperactive forms of GCM2 may contribute to later parathyroid hyperactivity or tumorigenesis. The expression of the CaSR––the calciostat––is regulated physiologically and pathophysiologically at the gene level.